High-strength high-conductivity self-lubricating dispersion strengthened copper composite material and preparation method thereof

By introducing nano W particles and submicron MnS particles in situ into the copper matrix, combining molding, phase change sintering and hot extrusion processes, high-strength, high conductivity, and high wear resistance copper-based composite materials were prepared, which solved the problem of synergistic improvement of copper alloy performance in the prior art and achieved significant improvement in performance.

CN119876684AActive Publication Date: 2025-04-25UNIV OF SCI & TECH BEIJING

Patent Information

Application Number
CN202411971363.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-25
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

In the prior art, the thermal conductivity, mechanical properties, and friction and wear properties of copper alloys cannot be improved synergistically. The addition of dispersion strengthening metal oxides and doping elements can only improve one aspect of the performance, and the added doping elements is costly. The addition of ceramic dispersion strengthening phases and doping elements may require thermal deformation processing in the subsequent process, and the dispersion strengthening metal oxides require special preparation and other technical problems.

Method used

The Mn element is introduced into the copper matrix by atomizing powder to prepare Cu-Mn alloy powder, and mixed it with WS2 powder, and mechanical alloying is achieved through high-energy ball milling. The W and S elements are unequalized in the Cu-Mn alloy powder to reach a supersaturation state to obtain copper-based composite powder. The copper-based composite material with both strength and lubricating properties is prepared through processes such as forming, phase change sintering, and hot extrusion.

Benefits of technology

The excellent comprehensive performance of copper-based composite materials is achieved with high strength, high conductivity and high wear resistance, which is better than that of copper-based composite materials prepared by traditional processes. The friction coefficient is reduced by 30-80% compared with traditional alumina diffuse reinforced copper, and the comprehensive performance is increased by more than 50% compared with traditional diffuse reinforced copper.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119876684A_ABST
    Figure CN119876684A_ABST
Patent Text Reader

Abstract

The invention provides a high-strength high-conductivity self-lubricating dispersion strengthened copper composite material and a preparation method, and relates to the technical field of copper composite material powder metallurgy. The high-strength high-conductivity self-lubricating dispersion strengthened copper composite material comprises the following phase compositions: 2-10 wt% of W dispersion strengthened particles, 1-10 wt% of MnS self-lubricating particles and the balance of a pure copper matrix, wherein the size of the W dispersion strengthening particles is 5-100 nm, the size of the MnS self-lubricating particles is 0.5-5 [mu] m, and the W dispersion strengthening particles and the MnS self-lubricating particles are evenly distributed in a copper matrix. The preparation method comprises the steps of micron-sized Cu-Mn alloy powder preparation, copper-based composite powder preparation, pressing forming, sintering and thermal deformation which are sequentially carried out. The method is simple and easy to operate, and has unique advantages in the aspect of preparing the self-lubricating dispersion strengthened copper composite material, the obtained composite material is excellent in structure performance, the sintering and extruding procedures are continuously completed, the manufacturing technological process is short, the production cost is low, and large-scale industrial production can be achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of copper composite material powder metallurgy, in particular to a high-strength and high-conductivity self-lubricating dispersion-strengthened copper composite material and a preparation method thereof. Background Art

[0002] Dispersion strengthening is a method of strengthening metals by adding or forming stable second-phase particles that are independent of the matrix. Nano-alumina dispersion-strengthened copper significantly improves the strength, hardness, and softening temperature of copper while retaining high electrical conductivity close to that of copper itself. It is the preferred material for resolving the contradiction between strength and conductivity and is widely used in high-tech fields that require both high strength and high conductivity, such as high-speed rail contact wires, resistance welding electrodes, conductive nozzles, and linear propulsion components of electromagnetic energy equipment. However, the above-mentioned fields are still faced with extreme environments of current-carrying friction and wear during service, and the friction and wear resistance of dispersion-strengthened copper needs to be improved.

[0003] At present, the methods to improve the friction and wear properties of copper alloys mainly include adding soft metals (such as Pb, Sn, etc.) and solid lubricants (such as graphite, sulfide, etc.). Soft metal elements such as Pb and Sn will dissolve into the copper matrix, causing lattice distortion, strongly increasing the electron scattering effect, and causing the electrical conductivity of the copper alloy to seriously decrease, which does not meet the use requirements. Adding solid lubricants such as graphite and sulfide to copper alloys can reduce the friction coefficient between the copper alloy and the friction couple, reduce the wear amount, and improve the friction and wear properties; however, the amount of solid lubricant added is large, which weakens the interface between the matrix and the lubricant, significantly reducing the strength, toughness and electrical conductivity of the copper alloy, especially sulfide lubricants such as MoS2 and WS2 will decompose at high temperatures, lose lubrication properties, and do not meet high temperature service requirements.

[0004] For example: Chinese patent CN107488793A discloses a high-conductivity dispersed copper-based high-temperature self-lubricating composite material and a preparation method thereof, which is prepared by designing the components of the composite material including oxygen-free copper powder and alumina dispersed copper powder, molybdenum disulfide powder, and graphite, and hot pressing and sintering after mixing; it is obvious that the alumina dispersed copper powder requires special preparation, which is costly and inefficient; and the alumina content in the alumina dispersed copper powder is low, and the effect of improving the mechanical properties is not significant. Although it can improve the wear resistance to a certain extent, the improvement, including the mechanical properties, is not large, and the same is true for molybdenum disulfide powder and graphite; and the conductivity is low.

[0005] Chinese patent CN102994799A discloses a copper-based self-lubricating composite material and its preparation method. It is necessary to add 2-4% yttrium barium copper oxide to the copper-based material to synergistically improve the conductivity, thermal stability and friction reduction and wear resistance. However, yttrium barium copper oxide can only play this role when it is of high purity. The market price of high-purity yttrium barium copper oxide is very high. For example, the Aladdin brand certified product, a 10-gram package with a purity of 99.9% and a particle size of ≤5μm is sold for about 1,516.90 yuan.

[0006] Chinese patent CN101956094A discloses a high-strength and high-conductivity dispersion-strengthened copper alloy and a preparation method thereof, which requires adding ceramic dispersion-strengthening phases and doping elements to the copper-based metal. Although this method can solve the problem of ceramic particle agglomeration caused by poor interface bonding between copper and ceramic, the problem of coarsening of ceramic particles during sintering, and the problem of decreased material conductivity caused by electron scattering at the interface between copper and ceramic, the particle size of the strengthening phase in the dispersion-strengthened copper alloy prepared by this method is nanometer-scale and the content is very low, making it difficult to improve the alloy's anti-friction and wear performance; in order to improve conductivity, the addition of high-cost doping elements is required.

[0007] Chinese patent CN101121974A discloses a high-strength and high-conductivity dispersion-strengthened copper alloy and a preparation method thereof. Not only is the preparation process complicated, but the added aluminum content is not much, not exceeding 1%, and alloy thin plates need to be prepared and internally oxidized, and finally laminated, hot pressed, hot extruded, and processed to obtain the desired product; therefore, the thickness of the product is 0.3-2.0 mm, the hardness and conductivity are generally improved, and the tensile strength is not effectively improved. Summary of the invention

[0008] In order to solve the technical problems that the thermal and electrical conductivity, mechanical properties, and friction and wear properties of copper alloys in the prior art cannot be improved synergistically, and only one aspect of the performance can be improved by adding dispersion-strengthened metal oxides and doping elements, and the added doping elements are costly, the addition of ceramic dispersion-strengthened phases and doping elements may require subsequent thermal deformation processing, and the dispersion-strengthened metal oxides require special preparation, the present invention proposes a high-strength, high-conductivity, self-lubricating dispersion-strengthened copper composite material and preparation method that can solve the above problems. The technical solution is as follows:

[0009] A high-strength and high-conductivity self-lubricating dispersion-strengthened copper composite material, which is in the shape of a rod, a plate, a tube or a complex-shaped component, and has a phase composition of 2-10wt% W dispersion-strengthened particles, 1-10wt% MnS self-lubricating particles, and the rest is a pure copper matrix; wherein: the W dispersion-strengthened particles have a size of 5-100nm, and the MnS self-lubricating particles have a size of 0.5-5μm, and are uniformly distributed in the copper matrix.

[0010] Optionally, in the phase composition of the high-strength and high-conductivity self-lubricating dispersion-strengthened copper composite material, the shape of the W dispersion-strengthened particles is spherical or ellipsoidal, and the shape of the MnS self-lubricating particles is nearly spherical, polygonal or irregular.

[0011] Optionally, the high-strength and high-conductivity self-lubricating dispersion-strengthened copper composite material has a hardness of HRB70-95, a thermal conductivity of 310-360 W / (m·K), a tensile strength of 500-650 MPa, a yield strength of 430-610 MPa, an elongation at break of 8-25%, and a conductivity of 80-90% IACS; using 7075 aluminum alloy as the friction pair, the friction coefficient is reduced by 30-80% compared with traditional alumina dispersion-strengthened copper.

[0012] A method for preparing the high-strength, high-conductivity, self-lubricating, dispersion-strengthened copper composite material is provided. The method for preparing the high-strength, high-conductivity, self-lubricating, dispersion-strengthened copper composite material comprises the following steps:

[0013] S1. Preparation of micron-sized Cu-Mn alloy powder: After electrolytic copper plates and electrolytic manganese ingots are vacuum-melted into alloy melt, micron-sized Cu-Mn alloy powder is prepared by atomization process;

[0014] S2, preparation of copper-based composite powder: S1 micron-sized Cu-Mn alloy powder is mixed with WS2 powder, and then high-energy ball milling is performed to achieve mechanical alloying to obtain copper-based composite powder;

[0015] S3, copper composite material green body pressing and forming: S2 copper-based composite powder is loaded into a mold and pressed and formed to obtain a copper composite material green body;

[0016] S4, sintering preparation of copper-based composite material sintered ingot: sintering the S3 copper-based composite material green body in a hydrogen atmosphere to obtain a copper-based composite material sintered ingot;

[0017] S5. Preparation of copper-based composite materials by thermal deformation: After the S4 copper-based composite material ingot is sintered, it is directly hot-extruded without cooling to obtain a fully densified copper-based composite material profile.

[0018] Optionally, the superheat temperature of the alloy melt in S1 is 100-250°C; the high-pressure atomization medium can be one or more of nitrogen, argon or water, and the atomization pressure is 2-25MPa; the average particle size of the micron-sized Cu-Mn alloy powder is 74-200μm, of which the Mn content is 0.7-7wt%, and the rest is pure copper.

[0019] Optionally, the high-energy ball milling method of S2 can be planetary ball milling, stirred ball milling, and vibration ball milling. The grinding ball material is one or more of alumina, zirconia, and agate. The ball-to-material ratio is 5:1-30:1, and the ball milling control agent is one or more of acetone, n-hexane, and dichloromethane. The rotation speed of the planetary ball mill and the stirred ball mill is 100-400rpm, the frequency of the vibration ball mill is 30-400Hz, the ball milling time is 12-48h, the average particle size of the WS2 powder is 0.1-10μm, and the content is 3-14wt%; the average particle size of the copper-based composite powder is 80-400μm.

[0020] Optionally, the material of the mold in S3 is rubber, silicone sheath or metal; the pressing forming is molding and cold isostatic pressing, the pressing pressure is 100-500MPa, and the holding time is 30-300s; the copper composite material green billet is used to make complex-shaped parts, rod billets, tube billets, plate billets and special-shaped billets.

[0021] Optionally, the sintering temperature in S4 is 700-900°C, the heating rate is 2-20°C / min, and the holding time is 1-5h; the relative density of the sintered ingot of the copper-based composite material is 95-99%, the hardness is HRB35-55, the thermal conductivity is 240-320W / (m·K), the tensile strength is 180-300MPa, the yield strength is 120-220MPa, the elongation at break is 5-20%, and the electrical conductivity is 70-90%IACS; using 7075 aluminum alloy as the friction pair, the friction coefficient is reduced by 30-50% compared with traditional alumina dispersion strengthened copper.

[0022] Optionally, the thermal deformation in S5 is hot extrusion, hot drawing or other thermal deformation processes.

[0023] Optionally, when the thermal deformation in S5 is hot extrusion, the extrusion ratio is 10:1-80:1; after hot extrusion, rods, wires or plates and strips of the composite material are obtained by drawing or cold rolling according to actual use needs.

[0024] Technical principle of the present invention:

[0025] The present invention introduces Mn element into a copper matrix by atomization powder making mode to obtain Cu-Mn alloy powder, mixes Cu-Mn alloy powder with WS2 powder, realizes mechanical alloying by high-energy ball milling, and W and S elements are non-equilibrium solid-dissolved in the Cu-Mn alloy powder to reach a supersaturated state to obtain a copper-based composite powder, and prepares a copper-based composite material with both strength and lubricity through processes such as forming, phase change sintering, and hot extrusion. During the sintering and heating process, nano W particles are precipitated from the copper-based composite powder to play a role of dispersion strengthening; Mn and S diffuse and combine to form submicron MnS particles, which are soft in nature. During the friction process with the friction couple, a layer of MnS film is formed on the surface of the friction couple to play a self-lubricating role. The precipitation of W and the diffusion and combination of MnS can reduce the lattice distortion energy of the copper matrix, and both are exothermic processes. The heat released by the two phase changes can promote sintering densification. The in-situ formed nano-W particles and submicron MnS particles maintain good incoherent interface bonding with the copper matrix, and have a weak effect on electron scattering. Through dual-phase synergistic strengthening, a high-strength, high-conductivity, and high-wear-resistant dispersion-strengthened copper composite material is obtained.

[0026] The present invention introduces two second phases, nano W particles and submicron MnS particles, into the copper matrix in situ, wherein the W particles play a role of dispersion strengthening and the MnS particles play a role of self-lubrication. The prepared self-lubricating dispersion-strengthened copper composite material has fine grains and has excellent comprehensive properties of high strength, high conductivity and high wear resistance, which is superior to the copper-based composite material prepared by traditional processes.

[0027] The present invention needs to control the atomization process parameters such as melt superheat and atomization pressure. This is because if the melt superheat is too high, the melt viscosity is reduced, and the atomization pressure is too high, which can easily lead to the Cu-Mn alloy powder being too fine; and the Cu-Mn alloy powder being too fine can easily lead to the following technical defects:

[0028] On the one hand, due to the fine particle size of WS2 powder, the mechanical alloying process with ultrafine Cu-Mn alloy powder is insufficient, resulting in WS2 residue, which will deteriorate the mechanical and conductive properties of the composite material; on the other hand, the ultrafine powder has poor fluidity, which affects the formability of the powder during the pressing process.

[0029] The key technical points of the present invention are:

[0030] Compared with the prior art, the above technical solution has at least the following beneficial effects:

[0031] The above scheme, the present invention proposes a high-strength and high-conductivity self-lubricating dispersion-strengthened copper composite material, which can solve the technical problems in the prior art that the thermal conductivity and electrical conductivity of copper alloys, the mechanical properties cannot be improved synergistically, by adding dispersion-strengthened metal oxides and doping elements, only one aspect of the performance can be improved, and the added doping elements are costly, the addition of ceramic dispersion-strengthened phases and doping elements may require subsequent thermal deformation processing, and the dispersion-strengthened metal oxides require special preparation.

[0032] The present invention uses vacuum induction melting to strictly control the melting process, thereby avoiding oxidation and burning of the Mn element and residual oxide inclusions in the alloy powder.

[0033] The invention selects the Mn element content so that the mechanically alloyed copper-based composite powder generates MnS particles of appropriate content in situ during the sintering process, which can play a good self-lubricating role and improve the friction and wear performance without seriously reducing the mechanical properties of the matrix.

[0034] The invention obtains Cu-Mn alloy powder with required particle size by strictly controlling atomization process parameters such as melt superheat, atomization pressure and the like.

[0035] The present invention controls the sintering temperature so that the copper grain size does not increase excessively and the W particles and MnS particles are kept at nanometer and submicron sizes respectively, thereby ensuring that the sintered ingot has high strength, high conductivity and excellent friction and wear properties after extrusion. The comprehensive performance is improved by more than 50% compared with traditional dispersion-strengthened copper.

[0036] The self-lubricating dispersion-strengthened copper composite material prepared by the present invention has fine grains, and has excellent comprehensive properties of high strength, high conductivity, and high wear resistance, and is superior to the copper-based composite material prepared by the traditional process.

[0037] The high-strength and high-conductivity self-lubricating dispersion-strengthened copper composite material prepared by the present invention has a hardness of HRB70-95, a thermal conductivity of 310-360 W / (m·K), a tensile strength of 500-650 MPa, a yield strength of 430-610 MPa, an elongation at break of 8-25%, and a conductivity of 80-90% IACS; with 7075 aluminum alloy as the friction pair, the friction coefficient is reduced by 30-80% compared with traditional alumina dispersion-strengthened copper.

[0038] In summary, compared with other traditional methods such as traditional chemical methods and mixing and adding, the method of the present invention prepares a dispersion-strengthened copper composite material with uniform component distribution, uniform performance, synergistically improved thermal conductivity and electrical conductivity, mechanical properties, and wear resistance through the preparation of micron-level Cu-Mn alloy powder, the preparation of copper-based composite powder, pressing, sintering, and thermal deformation; the method is simple and easy to operate, and has unique advantages in the preparation of self-lubricating dispersion-strengthened copper composite materials. The obtained composite material has excellent organizational properties, the sintering and extrusion processes are completed continuously, the manufacturing process flow is short, the production cost is low, and large-scale industrial production can be realized. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0040] Figure 1 This is a process flow chart of a high-strength, high-conductivity, self-lubricating, dispersion-strengthened copper composite material of the present invention;

[0041] Figure 2 This is a microstructure diagram of a high-strength, high-conductivity, self-lubricating, dispersion-strengthened copper composite material according to Example 1 of the present invention;

[0042] Figure 3 This is a microstructure diagram of a high-strength, high-conductivity, self-lubricating, dispersion-strengthened copper composite material according to Example 2 of the present invention;

[0043] Figure 4 This is a microstructure diagram of a high-strength, high-conductivity, self-lubricating, dispersion-strengthened copper composite material according to Example 3 of the present invention;

[0044] Figure 5 This is a microstructure diagram of a high-strength, high-conductivity, self-lubricating dispersion-strengthened copper composite material according to Example 4 of the present invention. DETAILED DESCRIPTION

[0045] The technical solution of the present invention is described below in conjunction with the accompanying drawings.

[0046] In the embodiments of the present invention, words such as "exemplarily" and "for example" are used to indicate examples, illustrations or explanations. Any embodiment or design described as "example" in the present invention should not be interpreted as being more preferred or more advantageous than other embodiments or designs. Specifically, the use of the word "example" is intended to present the concept in a specific way. In addition, in the embodiments of the present invention, the meaning expressed by "and / or" can be both, or it can be either of the two.

[0047] In the embodiments of the present invention, "image" and "picture" may sometimes be used interchangeably. It should be noted that when the distinction between them is not emphasized, the meanings they intend to express are consistent.

[0048] In the embodiments of the present invention, sometimes a subscript such as W1 may be written as a non-subscript such as W1. When the difference is not emphasized, the meanings to be expressed are the same.

[0049] In order to make the technical problems, technical solutions and advantages to be solved by the present invention more clear, a detailed description will be given below with reference to the accompanying drawings and specific embodiments.

[0050] A high-strength and high-conductivity self-lubricating dispersion-strengthened copper composite material, which is in the shape of a rod, a plate, a tube or a complex-shaped component, and has a phase composition of 2-10wt% W dispersion-strengthened particles, 1-10wt% MnS self-lubricating particles, and the rest is a pure copper matrix; wherein: the W dispersion-strengthened particles have a size of 5-100nm, and the MnS self-lubricating particles have a size of 0.5-5μm, and are uniformly distributed in the copper matrix.

[0051] In particular, in the phase composition of the high-strength and high-conductivity self-lubricating dispersion-strengthened copper composite material, the shape of the W dispersion-strengthened particles is spherical or ellipsoidal, and the shape of the MnS self-lubricating particles is nearly spherical, polygonal or irregular.

[0052] In particular, the high-strength and high-conductivity self-lubricating dispersion-strengthened copper composite material has a hardness of HRB70-95, a thermal conductivity of 310-360W / (m·K), a tensile strength of 500-650MPa, a yield strength of 430-610MPa, a fracture elongation of 8-25%, and a conductivity of 80-90%IACS; with 7075 aluminum alloy as the friction pair, the friction coefficient is reduced by 30-80% compared with traditional alumina dispersion-strengthened copper.

[0053] A method for preparing the high-strength, high-conductivity, self-lubricating, dispersion-strengthened copper composite material based on the above-mentioned method, the high-strength, high-conductivity, self-lubricating, dispersion-strengthened copper composite material is combined with Figure 1 Follow these steps:

[0054] S1. Preparation of micron-sized Cu-Mn alloy powder: After electrolytic copper plates and electrolytic manganese ingots are vacuum-melted into alloy melt, micron-sized Cu-Mn alloy powder is prepared by atomization process;

[0055] S2, preparation of copper-based composite powder: S1 micron-sized Cu-Mn alloy powder is mixed with WS2 powder, and then high-energy ball milling is performed to achieve mechanical alloying to obtain copper-based composite powder;

[0056] S3, copper composite material green body pressing and forming: S2 copper-based composite powder is loaded into a mold and pressed and formed to obtain a copper composite material green body;

[0057] S4, sintering preparation of copper-based composite material sintered ingot: sintering the S3 copper-based composite material green body in a hydrogen atmosphere to obtain a copper-based composite material sintered ingot;

[0058] S5. Preparation of copper-based composite materials by thermal deformation: After the S4 copper-based composite material ingot is sintered, it is directly hot-extruded without cooling to obtain a fully densified copper-based composite material profile.

[0059] In particular, the superheat temperature of the alloy melt in S1 is 100-250°C; the high-pressure atomization medium can be one or more of nitrogen, argon or water, and the atomization pressure is 2-25MPa; the average particle size of the micron-sized Cu-Mn alloy powder is 74-200μm, of which the Mn content is 0.7-7wt%, and the rest is pure copper.

[0060] In particular, the high-energy ball milling method of S2 can be planetary ball milling, stirred ball milling, and vibration ball milling. The grinding ball material is one or more of alumina, zirconia, and agate. The ball-to-material ratio is 5:1-30:1, and the ball milling control agent is one or more of acetone, n-hexane, and dichloromethane. The rotation speed of the planetary ball mill and the stirred ball mill is 100-400rpm, the frequency of the vibration ball mill is 30-400Hz, the ball milling time is 12-48h, the average particle size of the WS2 powder is 0.1-10μm, and the content is 3-14wt%; the average particle size of the copper-based composite powder is 80-400μm.

[0061] In particular, the material of the mold in S3 is rubber, silicone sheath or metal; the pressing forming is molding and cold isostatic pressing, the pressing pressure is 100-500MPa, and the holding time is 30-300s; the copper composite material green billet is used to make complex-shaped parts, rod billets, tube billets, plate billets and special-shaped billets.

[0062] In particular, the sintering temperature in S4 is 700-900℃, the heating rate is 2-20℃ / min, and the holding time is 1-5h; the relative density of the sintered ingot of the copper-based composite material is 95-99%, the hardness is HRB35-55, the thermal conductivity is 240-320W / (m·K), the tensile strength is 180-300MPa, the yield strength is 120-220MPa, the elongation at break is 5-20%, and the conductivity is 70-90%IACS; using 7075 aluminum alloy as the friction pair, the friction coefficient is reduced by 30-50% compared with traditional alumina dispersion strengthened copper.

[0063] In particular, the thermal deformation in S5 is hot extrusion, hot drawing or other thermal deformation processes.

[0064] In particular, when the thermal deformation in S5 is hot extrusion, the extrusion ratio is 10:1-80:1; after hot extrusion, rods, wires or plates and strips of the composite material are obtained by drawing or cold rolling according to actual use needs.

[0065] Example 1

[0066] A high-strength and high-conductivity self-lubricating dispersion-strengthened copper composite material, which is a rod material, and has a phase composition of 3wt% W dispersion-strengthened particles, 3wt% MnS self-lubricating particles, and the rest is a pure copper matrix; wherein: the size of the W dispersion-strengthened particles is 5nm, the size of the MnS self-lubricating particles is 5μm, and they are uniformly distributed in the copper matrix.

[0067] A method for preparing the high-strength, high-conductivity, self-lubricating, dispersion-strengthened copper composite material is provided. The method for preparing the high-strength, high-conductivity, self-lubricating, dispersion-strengthened copper composite material comprises the following steps:

[0068] S1. Preparation of micron-sized Cu-Mn alloy powder: Electrolytic copper plates and electrolytic manganese ingots are vacuum smelted into alloy melt, and the superheat temperature of the alloy melt is 250°C; micron-sized Cu-Mn alloy powder with an average particle size of 74 μm is prepared by atomization process, wherein the content of Mn is 2wt%, and the rest is pure copper; the high-pressure atomization medium is water, and the atomization pressure is 25 MPa;

[0069] S2, preparation of copper-based composite powder: S1 micron-grade Cu-Mn alloy powder was mixed with 4wt% WS2 powder with an average particle size of 100nm, and then mechanical alloying was achieved by planetary ball milling. The grinding ball material was zirconia, the ball-to-material ratio was 10:1, the ball milling control agent was acetone, the ball milling speed was 200rpm, and the ball milling time was 48h, to obtain a copper-based composite powder with an average particle size of 80μm;

[0070] S3, copper composite material green body pressing: S2 copper-based composite powder is loaded into a cylindrical silica gel package with a size of φ60×60mm, and after packaging, cold isostatic pressing is performed with a pressing pressure of 100MPa and a holding time of 300s to obtain a cylindrical green body of copper composite material with a size of φ50×50mm;

[0071] S4, sintering preparation of copper-based composite material sintering billet: S3 copper composite material φ50×50mm cylindrical green body is sintered in hydrogen atmosphere, the sintering temperature is 700℃, the heating rate is 10℃ / min, the holding time is 2h, and the copper-based composite material sintering billet with a relative density of 98.7% is obtained;

[0072] S5. Preparation of copper-based composite materials by hot deformation: After sintering, the copper-based composite material sintered ingot with a relative density of 98.7% in S4 is directly hot extruded without cooling down, and the extrusion ratio is 30:1 to obtain a fully densified copper-based composite material profile.

[0073] like Figure 2 As shown, in the phase composition of the high-strength and high-conductivity self-lubricating dispersion-strengthened copper composite material prepared in this embodiment, the shape of the W dispersion-strengthened particles is spherical, and the shape of the MnS self-lubricating particles is polygonal.

[0074] The high-strength and high-conductivity self-lubricating dispersion-strengthened copper composite material prepared in this embodiment has a hardness of HRB72, a thermal conductivity of 360W / (m·K), a tensile strength of 516MPa, a yield strength of 451MPa, an elongation at break of 23%, and a conductivity of 89%IACS; with 7075 aluminum alloy as the friction pair, the friction coefficient is reduced by 36% compared with traditional alumina dispersion-strengthened copper.

[0075] Example 2

[0076] A high-strength and high-conductivity self-lubricating dispersion-strengthened copper composite material, which is a plate material, and has a phase composition of 7wt% W dispersion-strengthened particles, 7wt% MnS self-lubricating particles, and the rest is a pure copper matrix; wherein: the W dispersion-strengthened particles have a size of 100nm, the MnS self-lubricating particles have a size of 0.5μm, and are uniformly distributed in the copper matrix.

[0077] A method for preparing the high-strength, high-conductivity, self-lubricating, dispersion-strengthened copper composite material is provided. The method for preparing the high-strength, high-conductivity, self-lubricating, dispersion-strengthened copper composite material comprises the following steps:

[0078] S1. Preparation of micron-sized Cu-Mn alloy powder: Electrolytic copper plates and electrolytic manganese ingots are vacuum smelted into alloy melt, and the overheating temperature of the alloy melt is 100°C; micron-sized Cu-Mn alloy powder with an average particle size of 200 μm is prepared by atomization process, wherein the content of Mn is 5wt%, and the rest is pure copper; the high-pressure atomization medium is nitrogen, and the atomization pressure is 2MPa;

[0079] S2, preparation of copper-based composite powder: S1 micron-grade Cu-Mn alloy powder was mixed with 10wt% WS2 powder with an average particle size of 10μm, and then mechanical alloying was achieved by stirring ball milling. The grinding ball material was alumina, the ball-to-material ratio was 20:1, the ball milling control agent was n-hexane, the ball milling speed was 400rpm, and the ball milling time was 12h, to obtain a copper-based composite powder with an average particle size of 400μm;

[0080] S3, copper composite material green body pressing: S2 copper-based composite powder is loaded into a cylindrical silica gel package with a size of φ60×60mm, and after packaging, cold isostatic pressing is performed with a pressing pressure of 500MPa and a holding time of 30s to obtain a cylindrical green body of copper composite material with a size of φ50×50mm;

[0081] S4, sintering preparation of copper-based composite material sintering billet: S3 copper composite material φ50×50mm cylindrical green body is sintered in hydrogen atmosphere, the sintering temperature is 900℃, the heating rate is 5℃ / min, the holding time is 3h, and the copper-based composite material sintering billet with a relative density of 96.2% is obtained;

[0082] S5. Preparation of copper-based composite materials by hot deformation: After sintering, the copper-based composite material sintered ingot with a relative density of 96.2% in S4 is directly hot extruded without cooling down, and the extrusion ratio is 50:1 to obtain a fully densified copper-based composite material profile.

[0083] like Figure 3 As shown, in the phase composition of the high-strength and high-conductivity self-lubricating dispersion-strengthened copper composite material prepared in this embodiment, the shape of the W dispersion-strengthened particles is ellipsoidal, and the shape of the MnS self-lubricating particles is nearly spherical.

[0084] The high-strength and high-conductivity self-lubricating dispersion-strengthened copper composite material prepared in this embodiment has a hardness of HRB82, a thermal conductivity of 346W / (m·K), a tensile strength of 575MPa, a yield strength of 482MPa, an elongation at break of 17%, and a conductivity of 83%IACS; with 7075 aluminum alloy as the friction pair, the friction coefficient is reduced by 67% compared with the traditional alumina dispersion-strengthened copper.

[0085] Example 3

[0086] A high-strength and high-conductivity self-lubricating dispersion-strengthened copper composite material, which is in the shape of a tube and has a phase composition of 10wt% W dispersion-strengthened particles, 8.6wt% MnS self-lubricating particles, and the rest being a pure copper matrix; wherein: the W dispersion-strengthened particles have a size of 40nm, the MnS self-lubricating particles have a size of 2μm, and are uniformly distributed in the copper matrix.

[0087] A method for preparing the high-strength, high-conductivity, self-lubricating, dispersion-strengthened copper composite material is provided. The method for preparing the high-strength, high-conductivity, self-lubricating, dispersion-strengthened copper composite material comprises the following steps:

[0088] S1. Preparation of micron-sized Cu-Mn alloy powder: Electrolytic copper plates and electrolytic manganese ingots are vacuum smelted into alloy melt, and the overheating temperature of the alloy melt is 150°C; micron-sized Cu-Mn alloy powder with an average particle size of 100 μm is prepared by atomization process, wherein the content of Mn is 6wt%, and the rest is pure copper; the high-pressure atomization medium is argon gas, and the atomization pressure is 4MPa;

[0089] S2, preparation of copper-based composite powder: S1 micron-grade Cu-Mn alloy powder was mixed with 14wt% WS2 powder with an average particle size of 5μm, and then mechanical alloying was achieved by vibration ball milling. The grinding ball material was agate, the ball-to-material ratio was 30:1, the ball milling control agent was dichloromethane, the vibration ball milling frequency was 50Hz, and the ball milling time was 24h, to obtain a copper-based composite powder with an average particle size of 180μm;

[0090] S3, copper composite material green body pressing: S2 copper-based composite powder is loaded into a cylindrical silica gel package with a size of φ60×60mm, and after packaging, cold isostatic pressing is performed with a pressing pressure of 200MPa and a holding time of 60s to obtain a cylindrical green body of copper composite material with a size of φ50×50mm;

[0091] S4. Preparation of sintered ingot of copper-based composite material: Sinter the cylindrical green body of S3 copper-based composite material with a size of φ50×50 mm in a hydrogen atmosphere at a sintering temperature of 850°C, a heating rate of 5°C / min, and a holding time of 3h to obtain a sintered ingot of copper-based composite material with a relative density of 99%;

[0092] S5. Preparation of copper-based composite materials by thermal deformation: After sintering, the copper-based composite material sintered ingot with a relative density of 99% in S4 is directly hot-extruded without cooling down, and the extrusion ratio is 80:1 to obtain a fully densified copper-based composite material profile.

[0093] like Figure 4 As shown, in the phase composition of the high-strength and high-conductivity self-lubricating dispersion-strengthened copper composite material prepared in this embodiment, the shapes of the W dispersion-strengthened particles are spherical and ellipsoidal, and the shapes of the MnS self-lubricating particles are nearly spherical and irregular.

[0094] The high-strength and high-conductivity self-lubricating dispersion-strengthened copper composite material prepared in this embodiment has a hardness of HRB91, a thermal conductivity of 317W / (m·K), a tensile strength of 622MPa, a yield strength of 584MPa, an elongation at break of 11%, and a conductivity of 81%IACS; with 7075 aluminum alloy as the friction pair, the friction coefficient is reduced by 80% compared with traditional alumina dispersion-strengthened copper.

[0095] Example 4

[0096] A high-strength and high-conductivity self-lubricating dispersion-strengthened copper composite material, which is in the shape of a complex-shaped shaft sleeve part and has a phase composition of 5wt% W dispersion-strengthened particles, 2wt% MnS self-lubricating particles, and the rest being a pure copper matrix; wherein: the W dispersion-strengthened particles have a size of 25nm, the MnS self-lubricating particles have a size of 3μm, and are uniformly distributed in the copper matrix.

[0097] A method for preparing the high-strength, high-conductivity, self-lubricating, dispersion-strengthened copper composite material is provided. The method for preparing the high-strength, high-conductivity, self-lubricating, dispersion-strengthened copper composite material comprises the following steps:

[0098] S1. Preparation of micron-sized Cu-Mn alloy powder: Electrolytic copper plates and electrolytic manganese ingots are vacuum smelted into alloy melt, and the overheating temperature of the alloy melt is 200°C; micron-sized Cu-Mn alloy powder with an average particle size of 74 μm is prepared by atomization process, wherein the content of Mn is 1.5wt%, and the rest is pure copper; the high-pressure atomization medium can be nitrogen, and the atomization pressure is 4MPa;

[0099] S2, preparation of copper-based composite powder: S1 micron-grade Cu-Mn alloy powder was mixed with 6.5wt% WS2 powder with an average particle size of 1μm, and then mechanical alloying was achieved by planetary ball milling. The grinding ball material was zirconia, the ball-to-material ratio was 15:1, the ball milling control agent was acetone, the ball milling speed was 270rpm, and the ball milling time was 30h, to obtain a copper-based composite powder with an average particle size of 82μm;

[0100] S3, copper composite material green body pressing forming: S2 copper-based composite powder is loaded into a GCr15 alloy mold for molding, the pressing pressure is 500MPa, the pressure holding time is 60s, and the copper composite material green body is obtained; the copper composite material green body is used to make complex-shaped shaft sleeve parts;

[0101] S4. Preparation of sintered ingot of copper-based composite material: The S3 copper-based composite material green body is sintered in a hydrogen atmosphere at a sintering temperature of 900° C., a heating rate of 5° C. / min, and a holding time of 3 h to obtain a sintered ingot of copper-based composite material.

[0102] like Figure 5 As shown, in the phase composition of the high-strength and high-conductivity self-lubricating dispersion-strengthened copper composite material prepared in this embodiment, the shape of the W dispersion-strengthened particles is ellipsoidal, and the shape of the MnS self-lubricating particles is irregular.

[0103] The high-strength and high-conductivity self-lubricating dispersion-strengthened copper composite material prepared in this embodiment has a relative density of 98.6%, a hardness of HRB47, a thermal conductivity of 286W / (m·K), a tensile strength of 273MPa, a yield strength of 180MPa, an elongation at break of 12%, and a conductivity of 76%IACS; with 7075 aluminum alloy as the friction pair, the friction coefficient is reduced by 43% compared with the traditional alumina dispersion-strengthened copper.

[0104] Example 5

[0105] A copper-based composite material with the same phase composition as in Example 1 was prepared. When other process conditions were the same, the sintering preparation process of the copper-based composite material sintered ingot was adjusted to: the sintering temperature was 600°C, the heating rate was 50°C / min, and the holding time was 2h, to obtain a copper-based composite material sintered ingot with a relative density of 78.9%.

[0106] The copper-based composite material prepared in this embodiment has a hardness of HRB53, a thermal conductivity of 272W / (m·K), a tensile strength of 340MPa, a yield strength of 198MPa, a fracture elongation of 13%, and a conductivity of 74%IACS; with 7075 aluminum alloy as the friction pair, the friction coefficient is reduced by 26% compared with the traditional alumina dispersion-strengthened copper. In comparison, the comprehensive performance of the copper-based composite material prepared in this embodiment is significantly lower than that of Example 1.

[0107] Example 6

[0108] A high-strength, high-conductivity, self-lubricating dispersion-strengthened copper composite material is prepared by the same process steps as Example 2. The high-strength, high-conductivity, self-lubricating dispersion-strengthened copper composite material is a plate, and its phase composition is: 1wt% W dispersion-strengthened particles, 20wt% MnS self-lubricating particles, and the rest is a pure copper matrix; wherein: the size of the W dispersion-strengthened particles is 8nm, and the size of the MnS self-lubricating particles is 28μm.

[0109] In the copper-based composite material prepared in this embodiment, the distribution of MnS self-lubricating particles is obviously segregated; the copper-based composite material has a hardness of HRB44, a thermal conductivity of 259W / (m·K), a tensile strength of 246MPa, a yield strength of 160MPa, a fracture elongation of 4%, and a conductivity of 47%IACS; with 7075 aluminum alloy as the friction pair, the friction coefficient is reduced by 42% compared with the traditional alumina dispersion-strengthened copper. In comparison, the comprehensive performance of the copper-based composite material prepared in this embodiment is significantly lower than that of Example 2.

[0110] The above scheme, the present invention proposes a high-strength and high-conductivity self-lubricating dispersion-strengthened copper composite material, which can solve the technical problems in the prior art that the thermal conductivity and electrical conductivity of copper alloys, the mechanical properties cannot be improved synergistically, by adding dispersion-strengthened metal oxides and doping elements, only one aspect of the performance can be improved, and the added doping elements are costly, the addition of ceramic dispersion-strengthened phases and doping elements may require subsequent thermal deformation processing, and the dispersion-strengthened metal oxides require special preparation.

[0111] The present invention uses vacuum induction melting to strictly control the melting process, thereby avoiding oxidation and burning of the Mn element and residual oxide inclusions in the alloy powder.

[0112] The invention selects the Mn element content so that the mechanically alloyed copper-based composite powder generates MnS particles of appropriate content in situ during the sintering process, which can play a good self-lubricating role and improve the friction and wear performance without seriously reducing the mechanical properties of the matrix.

[0113] The invention obtains Cu-Mn alloy powder with required particle size by strictly controlling atomization process parameters such as melt superheat, atomization pressure and the like.

[0114] The present invention controls the sintering temperature so that the copper grain size does not increase excessively and the W particles and MnS particles are kept at nanometer and submicron sizes respectively, thereby ensuring that the sintered ingot has high strength, high conductivity and excellent friction and wear properties after extrusion. The comprehensive performance is improved by more than 50% compared with traditional dispersion-strengthened copper.

[0115] The self-lubricating dispersion-strengthened copper composite material prepared by the present invention has fine grains, and has excellent comprehensive properties of high strength, high conductivity, and high wear resistance, and is superior to the copper-based composite material prepared by the traditional process.

[0116] The high-strength and high-conductivity self-lubricating dispersion-strengthened copper composite material prepared by the present invention has a hardness of HRB70-95, a thermal conductivity of 310-360 W / (m·K), a tensile strength of 500-650 MPa, a yield strength of 430-610 MPa, an elongation at break of 8-25%, and a conductivity of 80-90% IACS; with 7075 aluminum alloy as the friction pair, the friction coefficient is reduced by 30-80% compared with traditional alumina dispersion-strengthened copper.

[0117] In summary, compared with other traditional methods such as traditional chemical methods and mixing and adding, the method of the present invention prepares a dispersion-strengthened copper composite material with uniform component distribution, uniform performance, synergistically improved thermal conductivity and electrical conductivity, mechanical properties, and wear resistance through the preparation of micron-level Cu-Mn alloy powder, the preparation of copper-based composite powder, pressing, sintering, and thermal deformation; the method is simple and easy to operate, and has unique advantages in the preparation of self-lubricating dispersion-strengthened copper composite materials. The obtained composite material has excellent organizational properties, the sintering and extrusion processes are completed continuously, the manufacturing process flow is short, the production cost is low, and large-scale industrial production can be realized.

[0118] It should be understood that the term "and / or" in this article is only a description of the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship, but it may also indicate an "and / or" relationship. Please refer to the context for specific understanding.

[0119] In the present invention, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, at least one of a, b, or c can mean: a, b, c, ab, ac, bc, or abc, where a, b, and c can be single or multiple.

[0120] It should be understood that in various embodiments of the present invention, the size of the serial numbers of the above-mentioned processes does not mean the order of execution. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present invention.

[0121] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A high-strength, high-conductivity, self-lubricating, dispersion-strengthened copper composite material, characterized in that: The high-strength and high-conductivity self-lubricating dispersion-strengthened copper composite material is in the shape of a rod, a plate, a tube or a complex-shaped component, and has a phase composition of 2-10wt% W dispersion-strengthened particles, 1-10wt% MnS self-lubricating particles, and the rest is a pure copper matrix; wherein: the size of the W dispersion-strengthened particles is 5-100nm, the size of the MnS self-lubricating particles is 0.5-5μm, and they are uniformly distributed in the copper matrix.

2. The high-strength and high-conductivity self-lubricating dispersion-strengthened copper composite material according to claim 1, characterized in that: In the phase composition of the high-strength and high-conductivity self-lubricating dispersion-strengthened copper composite material, the W dispersion-strengthened particles are spherical or ellipsoidal in shape, and the MnS self-lubricating particles are nearly spherical, polygonal or irregular in shape.

3. The high-strength and high-conductivity self-lubricating dispersion-strengthened copper composite material according to claim 1, characterized in that: The high-strength and high-conductivity self-lubricating dispersion-strengthened copper composite material has a hardness of HRB70-95, a thermal conductivity of 310-360W / (m·K), a tensile strength of 500-650MPa, a yield strength of 430-610MPa, a fracture elongation of 8-25%, and a conductivity of 80-90%IACS; with 7075 aluminum alloy as the friction pair, the friction coefficient is reduced by 30-80% compared with traditional alumina dispersion-strengthened copper.

4. A method for preparing the high-strength, high-conductivity, self-lubricating, dispersion-strengthened copper composite material according to any one of claims 1 to 3, characterized in that: The preparation method of the high-strength and high-conductivity self-lubricating dispersion-strengthened copper composite material comprises the following steps: S1. Preparation of micron-sized Cu-Mn alloy powder: After electrolytic copper plates and electrolytic manganese ingots are vacuum-melted into alloy melt, micron-sized Cu-Mn alloy powder is prepared by atomization process; S2, preparation of copper-based composite powder: S1 micron-sized Cu-Mn alloy powder is mixed with WS2 powder, and then high-energy ball milling is performed to achieve mechanical alloying to obtain copper-based composite powder; S3, copper composite material green body pressing and forming: S2 copper-based composite powder is loaded into a mold and pressed and formed to obtain a copper composite material green body; S4, sintering preparation of copper-based composite material sintered ingot: sintering the S3 copper-based composite material green body in a hydrogen atmosphere to obtain a copper-based composite material sintered ingot; S5. Preparation of copper-based composite materials by thermal deformation: After the S4 copper-based composite material ingot is sintered, it is directly hot-extruded without cooling to obtain a fully densified copper-based composite material profile.

5. The method for preparing the high-strength and high-conductivity self-lubricating dispersion-strengthened copper composite material according to claim 1, characterized in that: The superheat temperature of the alloy melt in S1 is 100-250°C; the high-pressure atomization medium can be one or more of nitrogen, argon or water, and the atomization pressure is 2-25MPa; the average particle size of the micron-grade Cu-Mn alloy powder is 74-200μm, of which the content of Mn is 0.7-7wt%, and the rest is pure copper.

6. The method for preparing the high-strength and high-conductivity self-lubricating dispersion-strengthened copper composite material according to claim 1, characterized in that: The medium and high energy ball milling method of S2 can be planetary ball milling, stirring ball milling, and vibration ball milling. The grinding ball material is one or more of aluminum oxide, zirconium oxide, and agate. The ball-to-material ratio is 5:1-30:

1. The ball milling control agent is one or more of acetone, n-hexane, and dichloromethane. The rotation speed of the planetary ball mill and the stirring ball mill is 100-400rpm, the frequency of the vibration ball mill is 30-400Hz, and the ball milling time is 12-48h. The average particle size of WS2 powder is 0.1-10μm, and the content is 3-14wt%; the average particle size of the copper-based composite powder is 80-400μm.

7. The method for preparing the high-strength and high-conductivity self-lubricating dispersion-strengthened copper composite material according to claim 1, characterized in that: The material of the mold in S3 is rubber, silicone sheath or metal; the pressing forming is molding and cold isostatic pressing, the pressing pressure is 100-500MPa, and the holding time is 30-300s; the copper composite material green billet is used to make complex-shaped parts, rod billets, tube billets, plate billets and special-shaped billets.

8. The method for preparing the high-strength and high-conductivity self-lubricating dispersion-strengthened copper composite material according to claim 1, characterized in that: The sintering temperature in S4 is 700-900℃, the heating rate is 2-20℃ / min, and the holding time is 1-5h; the relative density of the sintered ingot of the copper-based composite material is 95-99%, the hardness is HRB35-55, the thermal conductivity is 240-320W / (m·K), the tensile strength is 180-300MPa, the yield strength is 120-220MPa, the elongation at break is 5-20%, and the conductivity is 70-90%IACS; using 7075 aluminum alloy as the friction pair, the friction coefficient is reduced by 30-50% compared with traditional alumina dispersion strengthened copper.

9. The method for preparing the high-strength and high-conductivity self-lubricating dispersion-strengthened copper composite material according to claim 1, characterized in that: The thermal deformation in S5 is hot extrusion, hot drawing or other thermal deformation processes.

10. The method for preparing the high-strength and high-conductivity self-lubricating dispersion-strengthened copper composite material according to claim 1, characterized in that: When the hot deformation in S5 is hot extrusion, the extrusion ratio is 10:1-80:1; after hot extrusion, rods, wires or plates and strips of the composite material are obtained by drawing or cold rolling according to actual use needs.

Citation Information

Patent Citations

  • High-strength high-conduction strengthened dispersion copper alloy and preparation method thereof

    CN101121974A

  • High-strength and high-conductivity dispersion-strengthened alloy and preparation method thereof

    CN101956094A

  • Copper-based self-lubricating composite material and preparation method thereof

    CN102994799A

  • High-conductivity dispersed copper-based high-temperature self-lubricating composite and preparation method thereof

    CN107488793A

  • Nanometer metal particle dispersion strengthening copper alloy and preparation method

    CN117947305A

Cited By

  • Flexible metal net composite self-lubricating material and preparation method thereof

    CN122232261A